Confident, valued and supported: Examining the benefits of employment support for military spouses. Issue 3 (3rd May 2020) - Godier-McBard, Lauren R.; Caddick, Nick; Fossey, Matt
ABSTRACT: Military spouses face numerous challenges in obtaining employment as a result of their connection to the military. Previous research has linked military spouses underemployment to reduced well-being and satisfaction with military life, which in turn impacts on retention of the service person. In response to this the UK Ministry of Defence (MOD) trialed a 2 year programme of employment support for spouses in 2015. This paper reports the findings of a qualitative evaluation of this programme and its impact on spouses. Interviews were carried out with 30 spouses and 23 of their serving partners to examine the benefits and impact of the support provided. The majority of spouses and their serving partners perceived the employment support as providing a positive contribution from the military to help spouses get back into employment or improve their employability. Additionally, spouses felt invested in by the military and valued as constituents in their own right. No impact of employment support for spouses on the intention to remain or leave the Armed Forces was identified. Longitudinal follow up will be required to determine any long-term impact of employment support on employment outcomes and retention.